2019
DOI: 10.1016/j.trre.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and outcomes of alcohol use after single solid organ transplantation: A systematic review and meta-analysis

Abstract: Background: Reviews on alcohol use in transplant recipients focus on liver recipients and their risk of post-transplant rejection, but do not assess alcohol use in kidney, heart, or lung transplant recipients. This systematic review and meta-analysis aims to synthesize the evidence on correlates and outcomes of any alcohol use and at-risk drinking after solid organ transplantation (Tx). Methods: We searched 4 databases for quantitative studies in adult heart, liver, kidney and lung Tx recipients, investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…This proportion is five times higher than the 6% reported in the report of the National Health Survey of Belgium, 35 yet the latter used different questions. The percentage observed within our heart transplant program is also twice as high as the 15% at‐risk drinking reported in a recently published meta‐analysis in solid organ transplantation 36 . Yet, studies almost exclusively focused on liver transplant patients, a population known to include a significant portion of patients with a history of alcohol‐related problems who are closely monitored to prevent alcohol use relapse post‐transplant.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This proportion is five times higher than the 6% reported in the report of the National Health Survey of Belgium, 35 yet the latter used different questions. The percentage observed within our heart transplant program is also twice as high as the 15% at‐risk drinking reported in a recently published meta‐analysis in solid organ transplantation 36 . Yet, studies almost exclusively focused on liver transplant patients, a population known to include a significant portion of patients with a history of alcohol‐related problems who are closely monitored to prevent alcohol use relapse post‐transplant.…”
Section: Discussionmentioning
confidence: 89%
“…at-risk drinking reported in a recently published meta-analysis in solid organ transplantation. 36 in liver transplant candidates, and that its presence often remains unnoticed without formal assessment. We will explore whether the AUDIT-C can be used successfully in transplant candidates also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Smoking in turn was found to be a risk factor for post-transplant at-risk drinking, while post-transplant alcohol use in general could be linked with male gender, being employed, and a history of psychiatric illness, among others. 35 No significant risk factors were found for low physical exercise. 36 Most of these studies are based on the results of kidney recipients, while research on heart recipients is rare.…”
Section: Introductionmentioning
confidence: 94%
“…8 Emerging literature has shown that nonadherence to nonpharmacological health-related behaviors posttransplant, negatively impacts morbidity and mortality and the determinants of behaviors. [9][10][11][12][13][14][15][16][17][18][19] According to the International Society for Heart and Lung Transplantation's (ISHLT) registry the median survival, conditional on survival to 1 year, for adult recipients overall, is 13.9 years with females surviving longer than males, 14.8 years versus 13.6 years, respectively. 16 A large cohort study of heart recipients reported that females were less likely to have diabetes mellitus, hypertension, peripheral vascular disease, tobacco use, prior cardiovascular surgery and were less supported by an intra-aortic balloon pump or durable ventricular assist device than males but were more likely to have a history of malignancy or require intravenous inotropes.…”
mentioning
confidence: 99%